Do nutrient standards support ecological status? A two-step diagnostic framework for evaluation - Geoff Phillips; Gary Free; Martyn G. Kelly; Heliana Teixeira; Gábor Várbíró; Agnieszka Kolada; Anne Lyche Solheim; Jens Fölster; Ioanna Varkitzi; Sandra Mingarelli (Water Research, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Linking gut, heart and metabolic health through cholesterol conversion by Akkermansia muciniphila - Negin Kazemian; Ramin Karimianghadim; S. Amirhossein Golzan; Nitin; Jackline D.W. Irungu; Geoff B. Coombs; Jonathan Low; Jonathan P. Little; Wesley F. Zandberg; Frank Halperin; Kirk Bergstrom; Avirup Guha; et al. (Chemical Engineering Journal, 2025)

Extreme enriched-mantle (EM) compositions recorded by the Sr-Nd-Hf isotopes of global cratonic lamproites - Soumendu Sarkar; Hayden Dalton; Andrea Giuliani; David Phillips; D. Graham Pearson; Geoff M. Nowell; Jon D. Woodhead; Janet Hergt; Roland Maas; A. Lynton Jaques; N.V. Chalapathi Rao; Yaakov Weiss; et al. (Geochimica et Cosmochimica Acta, 2025)

Setting nutrient boundaries to protect aquatic communities: The importance of comparing observed and predicted classifications using measures derived from a confusion matrix - Geoff Phillips; Heliana Teixeira; Martyn G. Kelly; Fuensanta Salas Herrero; Gábor Várbíró; Anne Lyche Solheim; Agnieszka Kolada; Gary Free; Sandra Poikane (Science of The Total Environment, 2024)

Open-source, fully-automated hybrid cardiac substructure segmentation: development and optimisation - Robert N. Finnegan; Vicky Chin; Phillip Chlap; Ali Haidar; James Otton; Jason Dowling; David I. Thwaites; Shalini K. Vinod; Geoff P. Delaney; Lois Holloway (Physical and Engineering Sciences in Medicine, 2023)
Radiotherapy for thoracic and breast tumours is associated with a range of cardiotoxicities. Emerging evidence suggests cardiac substructure doses may be more predictive of specific outcomes, however, quantitative data necessary to develop clinical planning constraints is lacking. Retrospective analysis of patient data is required, which relies on accurate segmentation of cardiac substructures. In this study, a novel model was designed to deliver reliable, accurate, and anatomically consistent segmentation of 18 cardiac substructures on computed tomography (CT) scans. Thirty manually contoured CT scans were included. The proposed multi-stage method leverages deep learning (DL), multi-atlas mapping, and geometric modelling to automatically segment the whole heart, cardiac chambers, great vessels, heart valves, coronary arteries, and conduction nodes. Segmentation performance was evaluated using the Dice similarity coefficient (DSC), mean distance to agreement (MDA), Hausdorff distance (HD), and volume ratio. Performance was reliable, with no errors observed and acceptable variation in accuracy between cases, including in challenging cases with imaging artefacts and atypical patient anatomy. The median DSC range was 0.81–0.93 for whole heart and cardiac chambers, 0.43–0.76 for great vessels and conduction nodes, and 0.22–0.53 for heart valves. For all structures the median MDA was below 6 mm, median HD ranged 7.7–19.7 mm, and median volume ratio was close to one (0.95–1.49) for all structures except the left main coronary artery (2.07). The fully automatic algorithm takes between 9 and 23 min per case. The proposed fully-automatic method accurately delineates cardiac substructures on radiotherapy planning CT scans. Robust and anatomically consistent segmentations, particularly for smaller structures, represents a major advantage of the proposed segmentation approach. The open-source software will facilitate more precise evaluation of cardiac doses and risks from available clinical datasets. Graphical abstract

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Combating cyanobacterial proliferation by avoiding or treating inflows with high P load—experiences from eight case studies - Jutta Fastner; Sally Abella; Arni Litt; Giuseppe Morabito; Lajos Vörös; Károly Pálffy; Dietmar Straile; Reiner Kümmerlin; David Matthews; M. Geoff Phillips; Ingrid Chorus (Aquatic Ecology, 2016)

Ecological status assessment of European lakes: a comparison of metrics for phytoplankton, macrophytes, benthic invertebrates and fish - Anne Lyche-Solheim; Christian K. Feld; Sebastian Birk; Geoff Phillips; Laurence Carvalho; Giuseppe Morabito; Ute Mischke; Nigel Willby; Martin Søndergaard; Seppo Hellsten; Agnieszka Kolada; Marit Mjelde; et al. (Hydrobiologia, 2013)

A phytoplankton trophic index to assess the status of lakes for the Water Framework Directive - Geoff Phillips; Anne Lyche-Solheim; Birger Skjelbred; Ute Mischke; Stina Drakare; Gary Free; Marko Järvinen; Caridad de Hoyos; Giuseppe Morabito; Sandra Poikane; Laurence Carvalho (Hydrobiologia, 2013)

Maximum growing depth of submerged macrophytes in European lakes - Martin Søndergaard; Geoff Phillips; Seppo Hellsten; Agnieszka Kolada; Frauke Ecke; Helle Mäemets; Marit Mjelde; Mattia M. Azzella; Alessandro Oggioni (Hydrobiologia, 2013)

Phytoplankton indicator taxa for reference conditions in Northern and Central European lowland lakes - Marko Järvinen; Stina Drakare; Gary Free; Anne Lyche-Solheim; Geoff Phillips; Birger Skjelbred; Ute Mischke; Ingmar Ott; Sandra Poikane; Martin Søndergaard; Agnieszka Pasztaleniec; Jeroen Van Wichelen; et al. (Hydrobiologia, 2013)

Defining Chlorophyll-a Reference Conditions in European Lakes - Sandra Poikāne; Maria Helena Alves; Christine Argillier; Marcel van den Berg; Fabio Buzzi; Eberhard Hoehn; Caridad de Hoyos; Ivan Karottki; Christophe Laplace-Treyture; Anne Lyche Solheim; José Ortiz-Casas; Ingmar Ott; et al. (Environmental Management, 2010)

Site-specific chlorophyll reference conditions for lakes in Northern and Western Europe - Laurence Carvalho; Angelo G. Solimini; Geoff Phillips; Olli-Pekka Pietiläinen; Jannicke Moe; Ana Cristina Cardoso; Anne Lyche Solheim; Ingmar Ott; Martin Søndergaard; Gianni Tartari; Seppo Rekolainen (Hydrobiologia, 2009)

Ecological threshold responses in European lakes and their applicability for the Water Framework Directive (WFD) implementation: synthesis of lakes results from the REBECCA project - Anne Lyche Solheim; Seppo Rekolainen; S. Jannicke Moe; Laurence Carvalho; Geoff Phillips; Robert Ptacnik; W. Ellis Penning; Laszlo G. Toth; Constance O’Toole; Ann-Kristin L. Schartau; Trygve Hesthagen (Aquatic Ecology, 2008)

Classifying aquatic macrophytes as indicators of eutrophication in European lakes - W. Ellis Penning; Marit Mjelde; Bernard Dudley; Seppo Hellsten; Jenica Hanganu; Agnieszka Kolada; Marcel van den Berg; Sandra Poikane; Geoff Phillips; Nigel Willby; Frauke Ecke (Aquatic Ecology, 2008)

Using aquatic macrophyte community indices to define the ecological status of European lakes - W. Ellis Penning; Bernard Dudley; Marit Mjelde; Seppo Hellsten; Jenica Hanganu; Agnieszka Kolada; Marcel van den Berg; Sandra Poikane; Geoff Phillips; Nigel Willby; Frauke Ecke (Aquatic Ecology, 2008)

Reconstructing nutrient histories in the Norfolk Broads, UK: implications for the role of diatom-total phosphorus transfer functions in shallow lake management - Helen Bennion; Peter G. Appleby; Geoff L. Phillips (Journal of Paleolimnology, 2001)

Practical application of 25 years' research into the management of shallow lakes - Geoff Phillips; Alison Bramwell; Jo Pitt; Julia Stansfield; Martin Perrow (Hydrobiologia, 1999)

The practical importance of the interactions between fish, zooplankton and macrophytes in shallow lake restoration - Martin R. Perrow; Adrian J.D. Jowitt; Julia H. Stansfield; Geoff L. Phillips (Hydrobiologia, 1999)

Do rooted macrophytes increase sediment phosphorus release? - Debbie Stephen; Brian Moss; Geoff Phillips (Hydrobiologia, 1997)